Climate and Agriculture Network for Africa Training - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Participants from more than 10 organizations came together on 11 May 2015 to attend a workshop on web content management and social media visibility training at the International Livestock Research Institute (ILRI) in Nairobi. The training is aimed at increasing the variety of content on the Climate and Agriculture Network for Africa (CANA). The platform targets policy makers by providing the missing link to scientific research. Photos: S.Kilungu (CCAFS)